Experiments in applied chemistry: for engineering students - Rattan, Sunita (S.K.Kataria & Sons, 2008)
Experiments in applied chemistry: for engineering students / Rattan, Sunita. -- Patparganj,Delhi: S.K.Kataria & Sons, 2008 660 R237e2 2nd ed No. of Copies : 1